2016
DOI: 10.1371/journal.pone.0161852
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Differences between Diapausing and Non-Diapausing D. montana Females Reared under the Same Photoperiod and Temperature

Abstract: BackgroundA wide range of insects living at higher latitudes enter diapause at the end of the warm season, which increases their chances of survival through harsh winter conditions. In this study we used RNA sequencing to identify genes involved in adult reproductive diapause in a northern fly species, Drosophila montana. Both diapausing and non-diapausing flies were reared under a critical day length and temperature, where about half of the emerging females enter diapause enabling us to eliminate the effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 88 publications
(109 reference statements)
1
47
0
Order By: Relevance
“…Obp56g, Obp99a, Obp99b, Obp83g and Obp49a). Similar genes have been previously associated with diapause in D. montana (Kankare et al 2016). Obp99b is repressed by JH, which is produced by the CA (Yamamoto et al 2013) and was found to be up-regulated in diapause .…”
Section: /supporting
confidence: 79%
See 1 more Smart Citation
“…Obp56g, Obp99a, Obp99b, Obp83g and Obp49a). Similar genes have been previously associated with diapause in D. montana (Kankare et al 2016). Obp99b is repressed by JH, which is produced by the CA (Yamamoto et al 2013) and was found to be up-regulated in diapause .…”
Section: /supporting
confidence: 79%
“…Finally, biological functions, such as 'acid biosynthetic', 'acyl-CoA metabolism', 'oxido-reduction', that we identified here were associated with diapause in previous studies in other Drosophila species (Salminen et al 2015;Kankare et al 2016). Table 1.…”
Section: /mentioning
confidence: 70%
“…The three compounds melt at high temperatures, but n-nonacosane has a higher melting point (62-66°C) than that of n-tetracosane (48-54°C). Insect literature suggests that diapausing species over-express long-chain hydrocarbons (Benoit, 2010;Kankare et al, 2016) because they improve cuticle impermeability and help in avoiding desiccation (Chung and Carroll, 2015;Gibbs, 2011). Thus, the increased amount of longer hydrocarbon chains in A. coluzzii females collected from temporary breeding sites (n-nonacosane) could support the 'strong' aestivation strategy suggested for these mosquitoes during the dry season.…”
Section: Seasonal Changes In Cuticular Hydrocarbon Fingerprints Suggementioning
confidence: 99%
“…In the present study, D. melanogaster and D. montana have highly similar expression profiles for adult reproductive diapause, which is consistent with a single evolutionary origin. However, some of this similarity is probably driven simply by the comparison being between a fly with and without developed ovaries (Zhao et al ., ; Kankare et al ., ). Goto et al .…”
Section: Discussionmentioning
confidence: 97%